Y(OTf)3-Catalyzed Diastereoselective [3+2] Cycloaddition of N-Tosylaziridines and Imines; Efficient Synthesis of Multisubstituted Imidazolidines - Wu, Xingxing; Zhang, Junliang (Synthesis, 2012)
An efficient Y(OTf)3-catalyzed generation of azomethine ylides from donor–acceptor aziridines and their [3+2] cycloaddition with imines was developed. The method provides facile access to multisubstituted imidazolidines, which have been extensively used in organic synthesis. Furthermore, a three-component reaction on a gram scale and an asymmetric variation were also developed in this work.
Keywords: bond cleavage; cycloaddition; ylides; Lewis acid; stereoselectivity